PENGARUH PENGGUNAAN TEKNIK COPY THE MASTER TERHADAP KETERAMPILAN MENULIS CERPEN - Darwina, Amelia; Thahar, Harris Effendi; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2016)
ABSTRACT The purpose of the research is describing the influence of cooperative learning model think talk write type through picture series medium in writing short story skill for students at X grade of Senior High School 3 of Padang Panjang. The data of this research is result test score of writing short story skill by using technique copy the master. Data is collected by work method test. The result of this research is it has significance influence of technique copy the master in writing short story skill for students at X grade of Senior High School 3 of Padang Panjang which on 95% significance level by (n1+n2)-2 freedom degree that is thitung > ttabel (7,33 >1,67). H0 is refused and H1 is accepted because the result of hypothesis test going to show that thitung is bigger than ttabel. Kata Kunci: pengaruh, teknik copy the master, keterampilan menulis cerpen